The association of the post-resuscitation on-scene interval and patient outcomes after out-of-hospital cardiac arrest - Khan, Laiba; Hutton, Jacob; Yap, Justin; Dodek, Peter; Scheuermeyer, Frank; Asamoah-Boaheng, Michael; Heidet, Matthieu; Wall, Nechelle; Fordyce, Christopher B.; van Diepen, Sean; Christenson, Jim; Grunau, Brian (Resuscitation, 2023)
After resuscitation from out-of-hospital cardiac arrest (OHCA) by Emergency Medical Services (EMS), the amount of time that should be dedicated to pre-transport stabilization is unclear. We examined whether the time spent on-scene after return of spontaneous circulation (ROSC) was associated with patient outcomes. We examined consecutive adult EMS-treated OHCAs from the British Columbia Cardiac Arrest registry (January 1/2019-June 1/2021) that had on-scene ROSC (sustained to scene departure). The primary outcome was favourable neurological outcome (Cerebral Performance Category ≤ 2) at hospital discharge; secondary outcomes were re-arrest during transport and hospital-discharge survival. Using adjusted logistic regression models, we estimated the association between the post-resuscitation on-scene interval (divided into quartiles) and outcomes. Of 1653 cases, 611 (37%) survived to hospital discharge, and 523 (32%) had favourable neurological outcomes. The median post-resuscitation on-scene interval was 18.8 minutes (IQR:13.0–25.5). Compared to the first post-resuscitation on-scene interval quartile, neither the second (adjusted odds ratio [AOR] 1.19; 95% CI 0.72–1.98), third (AOR 1.10; 95% CI 0.67–1.81), nor fourth (AOR 1.54; 95% CI 0.93–2.56) quartiles were associated with favourable neurological outcomes; however, the fourth quartile was associated with a greater odds of hospital-discharge survival (AOR 1.73; 95% CI 1.05–2.85), and both the third (AOR 0.40; 95% CI 0.22–0.72) and fourth (AOR 0.44;95% CI 0.24–0.81) quartiles were associated with a lower odds of intra-transport re-arrest. Among resuscitated OHCAs, increased post-resuscitation on-scene time was not associated with improved neurological outcomes, but was associated with improved survival to hospital discharge and decreased intra-transport re-arrest.